Islamic Religion Teachers' Efforts In Improving the Literacy of Al-Qur'an of Elementary School Students - Sudirman Sudirman; Nurleli Ramli (Edumaspul: Jurnal Pendidikan, 2023)
The ability to read and write the Qur'an for students at school is the shared responsibility of teachers who are Muslim, but Islamic religion teachers have a very large role because they are considered to have been equipped from college the ability to read, write, and understand the Qur'an properly. In addition, there are several learning materials that require students to be able to recognize hijaiyah letters, write hijaiyah letters, connect hijaiyah letters, and be able to read the Qur'an. Qur'anic literacy learning in schools is limited, therefore this study aims to find out what efforts are made by PAI teachers to improve the literacy of the Qur'an of Grade I and II Students of SD Negeri 82 Parepare City. The research was conducted using a qualitative method with a field research approach, where the research data was collected through interview techniques together with Islamic religion teachers and Principals. Data collection was also carried out through observation techniques of Al-Qur'an literacy learning activities taking place at school and identifying lesson plans and media used in Al-Qur'an literacy. The results showed that the efforts made by Islamic religion teachers in improving the Qur'an literacy skills of students in grades I and II are apperception activities utilized for a maximum of 10 minutes, every Friday for 1 hour of lessons, flash pesantren activities in the month of Ramadan for 1 week, and the introduction of letters.